Buddyz Islamic Collection / Nur Dahiyah Abd Ghani ...[et al.] - Abd Ghani, Nur Dahiyah; Md Salleh, Nur Athirah; Rahman, Norsyazani; Azali, Nur Azlina; Zainal Abidin, Norsazliana; Zainudin, Nur Fatin Nabihah (2015)
The operational plans are able for helping the organization to determine the operational process in making Muslim Attire. The manager has to prepare the operational schedule in order to enhance the smooth flow of the operation. Operational Executive is responsible to manage the business and more careful on managing the process and also to distribute products and service.